The chronology of Lapita ware in New Caledonia - Sand, Christophe
The Lapita ceramics that define the 'Lapita' cultural complex of the southwestern Pacific are named for the type-site of Lapita, on the south Melanesian island of Nouvelle-Calédonie (New Caledonia). The island archipelago's early sites are central to shaping what Lapita is, and — if Lapita is not alone — to how it meshes with the other precocious ceramics made by voyagers of the western Pacific. Varied radiocarbon determinations need to be collated, and some stratigraphic complications resolved.